Managing early blight disease in tomato - Singh, R K; Singh, Satyandra (Indian Horticulture, 2018)
Tomato is an easy and popular vegetable. It is difficult to save its crop from disease and pests. They are main hindrances in production of tomato. The early blight is second serious disease after tomato leaf curl virus disease. It is responsible for significant yield losses incurred each year. Screening of early blight resistant tomato varieties/lines is a single best remedy.